(untitled) (Publicaciones en Ciencias y Tecnología, 2012)
Using the Distributed Artificial Intelligence and the Distributed Robotics as a frame of reference, in this work are designed, developed and implemented algorithms to control autonomous, mobile, reactive, rational, proactive and sociable small robots. These minibots are capable to exhibit behaviors inspired in biological societies. Through the development of this work it was found that if the robot has to perform simple tasks, a reactive architecture is more convenient, efficient and effective. While for the performance of tasks of medium or greater complexity, is recommend the use of a hybrid architecture that allows the incorporation of deliberative reasoning.